Mexican melodrama : film and nation from the Golden Age to the new wave - Lahr-Vivaz, Elena (The University of Arizona Press, 2016)
"Mexican Melodrama offers a timely look at critically acclaimed films that serve as key referents in discussions of Mexican cinema. Elena Lahr-Vivaz artfully portrays the dominant conventions of historical and contemporary Mexican cinema, showing how new-wave directors draw from a previous generation to produce meaning in the present"--Provided by publisher.
Keywords: Motion pictures -- Mexico -- History.; Motion pictures, Mexican -- History and criticism.; Cinéma -- Mexique -- Histoire.; Cinéma mexicain -- Histoire et critique.; ART -- General.; Motion pictures; Motion pictures, Mexican; Mexico; Criticism, interpretation, etc.; History